POLITICAL CULTURE AND MODERNIZATION IN THE CENTRAL ASIAN STATES - DONONBAEV, Alim; NASKEEVA, Asel (CENTRAL ASIA AND THE CAUCASUS, 2004)
Their newly acquired sovereignty has turned the attention of the Central Asian countries toward nation-building. Throughout history, the nation-state has been responsible for consolidating society: previously disunited peoples became a closely-knit civil nation. The process went in three directions: ethnic groups joined together to form a civil society; economic progress helped overcome social and class distinctions, while rivaling groups pursuing opposite interests reached unity on vitally important issues.In Central Asia and elsewhere in the CIS the transition is creating numerous difficulties. Foreign researchers are trying to grasp the deep-rooted causes of these difficulties and critically assess our experience. An analysis of current socioeconomic dynamics and their possible future development suggested to certain foreign academics that the region “in fact lacks the necessary prerequisites” to move forward and that it is sinking “into a deep and protracted crisis” as a result of which the local states will degenerate into “failed countries.”1It goes without saying that the social and economic situation in all the Central Asian countries fighting for survival is still grave; the earlier optimistic forecasts proved to be unfounded.